Microneedle Patches: Present State, Challenges, and the Way Forward - Muhammad Irfan Siddique (Asian Journal of Pharmaceutics (AJP), 2025)
Transdermal drug delivery has gained significant attention as an alternative to conventional methods due to its non-invasive approach and potential to enhance patient compliance. Among the various techniques, microneedle (MN) patches have emerged as a revolutionary tool for effective drug delivery through the skin. These patches work by creating micro-scale channels in the skin, enabling the transport of therapeutic agents while minimizing pain, discomfort, and the risk of infection commonly associated with traditional injections. Recent developments in MN technology have focused on optimizing their design, fabrication, and material selection to improve efficiency, biocompatibility, and safety. Various types of MNs, such as solid, dissolvable, and hollow structures, have been developed to suit specific drug delivery applications. The use of biodegradable and bio-responsive materials has further expanded the scope of MN patches, enabling controlled and sustained release of drugs. This review explores the recent advancements in MN patch technology, highlighting innovative approaches that have been employed to enhance their clinical efficacy and scalability. Applications of MN patches span a wide range of therapeutic areas, including vaccine delivery, hormone therapy, and pain management, offering promising solutions to challenges in modern healthcare. However, despite these advantages, challenges, such as large-scale manufacturing, cost-effectiveness, and regulatory standardization continue to limit widespread clinical adoption. By bridging the gap between non-invasive techniques and efficient drug delivery, MN patches have the potential to transform transdermal therapy. This article aims to provide a comprehensive overview of present trends, challenges, and future perspectives in MN patch development, emphasizing their role as a key innovation in skinbased drug administration.